The Role of Quality Assurance in Pahang Halal Food Industry in Malaysia - Ida Rizyani, Tahir; Junaidu, Abubakar Sambo; Bashir, Muktar (Apex Journal International, 2015)
Malaysia in its effort towards developing its various products for consumption particularly Halal foods for both domestic as well as international market developed and launched what is reffered to as Malaysian Standard MS 1500 “General Guidelines on the Production, Preparation, Handling and storage of Halal food”. The reason behind it is the fact that Malaysia needed a platform that will improve the standard as well as the quality of its products for consumption particularly Halal food. Quality control is a key determinant that covers and influence success in all aspects of modern industry, services, as well as manufacturing and the essence of quality control is to achieve high level of customer satisfaction which will boost thebusiness performance. This Paper therefore, examined the capability of quality control towards enhancing business performance particularly in Halal food industry in Pahang. The specieficobjectives of this paper is to examine the relationship between quality control and business performance and also to identify mean difference and years in the industry. In order to generate data questioniers were distributed between the managers and the owners of the companies. Also, in this paper reliability and pearson correlation was employed as the method of analysis, the paper concludes that quality control is very vital to the survival of the company in particular and the economy of the country in general. Finally, the paper recommend that crucial attention must be given towards constant improvement of quality control process throughout organizations to ensure high ends deliverables especially when it involved food based products and services.